7+2(1-x)=5-2(3-4x)

Simple and best practice solution for 7+2(1-x)=5-2(3-4x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7+2(1-x)=5-2(3-4x) equation:


Simplifying
7 + 2(1 + -1x) = 5 + -2(3 + -4x)
7 + (1 * 2 + -1x * 2) = 5 + -2(3 + -4x)
7 + (2 + -2x) = 5 + -2(3 + -4x)

Combine like terms: 7 + 2 = 9
9 + -2x = 5 + -2(3 + -4x)
9 + -2x = 5 + (3 * -2 + -4x * -2)
9 + -2x = 5 + (-6 + 8x)

Combine like terms: 5 + -6 = -1
9 + -2x = -1 + 8x

Solving
9 + -2x = -1 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
9 + -2x + -8x = -1 + 8x + -8x

Combine like terms: -2x + -8x = -10x
9 + -10x = -1 + 8x + -8x

Combine like terms: 8x + -8x = 0
9 + -10x = -1 + 0
9 + -10x = -1

Add '-9' to each side of the equation.
9 + -9 + -10x = -1 + -9

Combine like terms: 9 + -9 = 0
0 + -10x = -1 + -9
-10x = -1 + -9

Combine like terms: -1 + -9 = -10
-10x = -10

Divide each side by '-10'.
x = 1

Simplifying
x = 1

See similar equations:

| -38=-2x-2x-10 | | 4x+7=-2x+-3 | | 2(4x+5)=2(4x-2)+14 | | 6(4x-10)=(x+10) | | -x-8=x+6 | | 4t^2=-24t | | 2(x+8)=9x+9-7x+7 | | x^2-8+16=16 | | 0=x^2+0.036x-0.00693 | | (2h)+2=26 | | 20x-4y-5z+7=0 | | -6(x+2)+7=1x+6 | | 3x=5-2(2+4x) | | 3x-14y=-49 | | -6t-7= | | 6(x+2)+7=1x+6 | | 2xy^2-xy=0 | | 3x+1+3x=67 | | (x-24)+29=360 | | 15+2x=12.5x+2.5 | | 3(y+4)=12 | | 2b-10=5-3b | | 12.5x=10.5 | | -6b=-5b+10 | | 2(y-8)=20 | | 7h=4+6h | | (7(x+5)-18)+(3(x-2)+4)= | | 12.3x-9.2=3x-0.7x | | x+(x*1.08)=188000 | | 7(-3+6x)=-21 | | 2x+3=5x-4+7 | | x^4+1500x^2+1250000=0 |

Equations solver categories